الروايات الإسرائيلية في التفسير، وخطورتها على الإسلام والمسلمين (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:Praise be to God, and prayer and peace be upon the Messenger of God. Objective: to shed some light on the factors that led to the leakage of Israelites in books of interpretation, and what are the reasons for their spread among the general public? How dangerous are they to Islam and Muslims? Methodology of study: Analytical, inductive. Significance of the Topic and Reasons for Choosing it: The Israelites have been inculcated in the Islamic heritage in general and in the interpretative heritage in particular, which has led to the corruption of the doctrine of some Muslims. They have portrayed Islam as a superstitious religion, meaning with nonsense and falsehoods without foundation. They have lost confidence in some of the Salafi scholars, and characterized the prophets in the most terrible way that belittled their infallibility, demeaned them, and distracted Muslims from the purpose for which the Qur'an had been revealed, so they had to be warned against all of this, with some examples. Results: Some Israelis have included superstitions and falsehoods in order to deter any human being, no matter how tolerant, in our age from entering Islam, and to make it look suspicious. Recommendations: Instruct religion students to care for these narratives in their scientific research (BA - MA — Ph.D.) to eventually come up with what could be an exclusivity for what we don't want to be included in books of interpretation and warn of it.المراجع References